PHYTOCHEMICAL EXTRACTIONS, QUALITATIVE ANALYSIS, AND EVALUATION OF ANTIMICROBIAL ACTIVITY IN THE LEAF AND STEM BARK OF SOLANUM PUBESCENS WILLD. - VN, SUDHAMA; M, RAMAKRISHNAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to extract the phytochemicals from leaf and stem bark of Solanum pubescens, perform qualitative analysis, and evaluate antimicrobial activity of the phytochemicals against certain microbial pathogens. Methods: Leaf and stem bark of S. pubescens was subjected to phytochemical extractions using Soxhlet apparatus with five different solvents, identified the major constituents in different solvent extracts using standard protocols and investigated the potential antimicrobial activities of the extracts against certain selected bacterial and fungal pathogens by agar well diffusion method. Results: The maximum yield was in methanolic extracts of leaf and stem bark of the study plant such as 18.51 and 12.5%, respectively, followed by the hydroalcohol extracts (14.23 and 10.00%). Qualitative phytochemical analysis revealed maximum number of extracted bioactive compounds when compared to other similar studies. Among the five different solvent extracts of S. pubescens, n-hexane extract of stem bark was found to be active against all the bacterial pathogens and stem bark extracts made with methanol and hydroalcohol showed antifungal activity against all the four fungal pathogens tested. Leaf extracts made with solvents such as n-hexane and ethyl acetate showed inhibition against Klebsiella pneumoniae and Staphylococcus aureus, respectively, hydroalcohol extract was active against Pseudomonas aeruginosa and Salmonella typhimurium while none of the leaf extracts of the study plant showed inhibition zones against fungal pathogens tested. Conclusion: Multiple solvent extraction approach yielded the phytochemicals which are not yet reported and the antimicrobial activities of phytochemicals acknowledged their medicinal value.